Turning off the tap: stopping tuberculosis transmission through active case-finding and prompt effective treatment - Yuen, Courtney M; Amanullah, Farhana; Dharmadhikari, Ashwin; Nardell, Edward A; Seddon, James A; Vasilyeva, Irina; Zhao, Yanlin; Keshavjee, Salmaan; Becerra, Mercedes C (The Lancet (British edition), 2015)
To halt the global tuberculosis epidemic, transmission must be stopped to prevent new infections and new cases. Identification of individuals with tuberculosis and prompt initiation of effective treatment to rapidly render them non-infectious is crucial to this task. However, in settings of high tuberculosis burden, active case-finding is often not implemented, resulting in long delays in diagnosis and treatment. A range of strategies to find cases and ensure prompt and correct treatment have been shown to be effective in high tuberculosis-burden settings. The population-level effect of targeted active case-finding on reducing tuberculosis incidence has been shown by studies and projected by mathematical modelling. The inclusion of targeted active case-finding in a comprehensive epidemic-control strategy for tuberculosis should contribute substantially to a decrease in tuberculosis incidence.